Investigation of Bioplastic Properties Developed from Acrylate Epoxidized Soybean Oil Through Ring Opening Polymerization Process - Hiew, Ming Yu; Gupta, Arun; Gupta, Ritu; Husain, Muhamed Saad Bala (Universiti Malaysia Pahang, 2017)
Soybean oil is one of the major vegetable oils containing more than 99% of triglycerides of saturated and unsaturated fatty acids and has become an interesting source to produce bioplastic. This study investigates the synthesis and characterization of bioplastic developed by the acrylate epoxidized soybean oil through ring opening polymerization process. The mechanical properties of the samples were characterized using Fourier Transform Infrared Spectroscopy, Thermo gravimetric analysis and the physio-chemical properties of the bioplastics were studied. In this study, the bioplastic made up from soybean oil with the lowest glycerol concentration showed the best mechanical properties.